USING MIND MAPPING IN WRITING DESCRIPTIVE TEXT FOR STUDENTS WITH DIFFERENT LEVELS OF ENGLISH WRITING SKILLS - Ridha Mardiani (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2022)
The aim of this research are to find out how mind mapping techniques can help and how students with different skills respond when using Mind Mapping in writing descriptive text activities. Writing is one of the basic skills that must be mastered by English learners. In fact, learners often have difficulty in writing activities, especially in conveying their ideas into written form. However, students' writing skills are not always the same skills. In this study, the writer used a case study with descriptive data analysis to achieve the goals of this research. The participants of the research were students from one of the vocational high schools in Cimahi with the writing skills on A1 and A2. The research instrument used in this research is learning log and interview. The result findings show that students with A1 and A2 abilities stated that the application of Mind Mapping techniques was helped them because they could formulate ideas when writing descriptive texts and also Mind Mapping was easy to use. There were difficulties faced by all participants, one of participant with skill level A1 had difficulty due to lack of ideas, and the other participant had difficulty in vocabulary. However, all participants A1 and A2 stated that Mind mapping is an interesting technique. In conclusion, Mind Mapping is easy to use and helps students in writing activities because they can arrange ideas from the main topic to the subtopic. In addition, students showed a positive response to the Mind Mapping technique.